Load compensation based on frame considering low-order dominant harmonics and distorted power system. (June 2016) - Fallah, Mehdi; Imani, Mitra; Abarzadeh, Mostafa; Kojabadi, Hossein Madadi; Hejri, Mohammad
Abstract: In this paper, by considering voltage distortion and frequency variation, the control strategy of synchronous reference frame (SRF) for three-phase shunt active power filter has been improved. In the SRF compensation method a conventional low pass filter (CLPF) is used to extract the dc component of the d -axis current ( I d ). Unfortunately in the presence of low-order harmonics of the load current (second and third ones), the transient response time is increased. If the amplitude of these harmonics are high, the distortions in CLPF output signal are increased, and as a result, the desired compensation cannot be achieved. In this paper to overcome this problem, a novel numerical LPF is designed and implemented based on variable forgetting factor-recursive least squares (VFF-RLS). The advantages of the proposed filter over CLPFs include independence of the load current harmonic components, fast dynamic and high accuracy of the response. Moreover, due to the malfunction of the conventional phase locked loop (PLL) in polluted and variable frequency environment, a second order generation integrator-frequency locked loop (SOGI-FLL) based on fuzzy logic controller (FLC) and wavelet transform (WT) is proposed. Effectiveness of the proposed method is evaluated with both simulations and experimental results in a three-phase power system.